Analisis Prediktor Perilaku Seksual: Studi Kasus Kesehatan Mental dan Dinamika Sosial Remaja di Kota Samarinda - Rea Ariyanti; Muhamad Zakki Saefurrohim; Agustin Putri Rahayu; Muh Amri Arfandi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Premarital sexual behaviour among adolescents has become a serious public health challenge, particularly with the rising cases of sexually transmitted infections and unintended pregnancies in Samarinda. The objective of this study is to analyse the factors associated with premarital sexual behavioural intentions among students at State Senior High School X Samarinda, considering both demographic aspects and current psychological conditions. The present study employed a quantitative approach with a cross-sectional design, and involved 125 respondents who were selected through a multistage random sampling technique. The data were collected through face-to-face interviews using the DASS-21 instrument, the Self-Harm Inventory, as well as scales for intention and peer pressure. The subsequent analysis employed multiple linear regression. The findings of the study indicated that intentions regarding sexual behaviour in the premarital context were found to be significantly influenced by grade level (p = 0.029) and peer pressure (p = 0.011). In the eleventh grade, students demonstrated a decline in intentions, whilst high levels of peer pressure resulted in an escalation in sexual intentions. It is noteworthy that psychological variables, including depression, self-control, and self-esteem, did not demonstrate a substantial impact in this model. The findings of this study indicate that sexual intention among adolescents in Samarinda is more situational-social in nature, rather than being merely an internal individual issue. It is recommended that educational institutions consider the implementation of enhanced peer education programmes and assertiveness skills training as a means of mitigating the potentially detrimental influences of the social environment.